Harmful algae diversity from a coastal upwelling system detected by high-throughput sequencing - Ríos-Castro, Raquel; Novoa, Beatriz; Hernández-Urcera, Jorge; Rodríguez, Francisco; Figueras, Antonio (Frontiers in Marine Science, 2023)
Introduction In recent years, environmental DNA (eDNA) amplicon sequencing has been used to unveil plankton diversity in the field. Nevertheless, molecular methods, such as this, are rarely used in harmful algal bloom (HAB) monitoring programs, which mainly rely on morphological identification by conventional light microscopy. Methods The present study focused on a shallow marine environment (Ría de Vigo, Northwest Spain), where sediment and plankton samples were collected from 2016 to 2018. Results The application of eDNA amplicon sequencing allowed us to simultaneously detect 25 potential harmful species (mainly diatoms and dinoflagellates) included in the IOC-UNESCO Taxonomic Reference List of Harmful Microalgae. Among these, causative agents of amnesic shellfish poisoning (Pseudo-nitzschia spp.) paralytic shellfish poisoning (Gymnodinium catenatum and Alexandrium minutum), azaspiracid producers (Azadinium poporum) and ichthyotoxic haptophytes (Chrysochromulina leadbeateri), were identified. Some toxic microalgae were better represented in sediment (e.g., Pseudo-nitzschia pungens, Gymnodinium catenatum) or planktonic fractions (e.g., Pseudo-nitzschia, Gymnodinium smaydae), confirming the importance of including both sediment and plankton fractions in eDNA monitoring studies. Despite the limitations of sequencing short amplicons, it was possible to discern in this study six Pseudo-nitzschia species and associate each of them with each seasonal peak produced in summer periods. Furthermore, several species previously unreported in Ría de Vigo (Pseudo-nitzschia turgidula, Chrysochromulina leadbeateri, Azadinium poporum) could be detected. Discusion These results point out the application of eDNA amplicon sequencing to expand our knowledge about harmful species in HAB monitoring programs and early warning systems for low abundant and rare taxa.